Irradiated Cities - mariko, nagai (punctum books, 2023)
The before, the after, and the event that divides. In Irradiated Cities, Mariko Nagai seeks the dividing events of nuclear catastrophe in Japan, exploring the aftermath of the bombings at Hiroshima and Nagasaki and the nuclear meltdown at Fukushima. Nagai's lyric textual fragments and stark black and white photographs act as a guide through these spaces of loss, silence, echo, devastation, and memory. And haunting each shard and each page an enduring irradiation, the deadly residue of catastrophe that leaks into our DNA. Winner of the 2015 NOS Book Contest, as selected by guest judge lê thi diem thúy.